Efficacy and safety of bortezomib-based retreatment at the first relapse in multiple myeloma patients: A retrospective study. Issue 7 (August 2015) - Oriol, Albert; Giraldo, Pilar; Kotsianidis, Ioannis; Couturier, Catherine; Olie, Robert; Angermund, Ralf; Corso, Alessandro
<x content-type="archive" xml:space="preserve">Abstract</x> Objective Multiple myeloma remains incurable and retreatment with available therapies is of substantial interest. Methods This retrospective observational study included data from 35 patients treated initially and at the first relapse with bortezomib-containing regimens. Results Bortezomib retreatment provided a similar depth and time to response as first-line therapy; however, as could be expected, the duration of response was shorter with retreatment. The tolerability profile was similar with bortezomib as the first- and second-line therapy, with no evidence of cumulative toxicity. Conclusion These findings support bortezomib retreatment after a treatment-free interval of ≥6 months in patients who achieved at least a partial response to the first-line bortezomib-based therapy.